Consequences of cystic fibrosis transmembrane regulator mutations on inflammatory cells - Grumelli, Sandra (2016)
Recent studies in cystic fibrosis (CF) transmembrane regulator (CFTR) mutations and function have shed light on its involvement in disease progression. The extent of cell and tissue distribution of CFTR facilitates systemic dysfunction of ion transport in patients carrying a mutation in CFTR, however, its incidences as cofounding risk factor to develop other diseases is not well studied. In this review we differentiate the dysfunctions driven by CFTR mutations in cell of the immune system and their role in CF progression and examine the types of medical treatments available to patients up to date.